Emergent Change in a Mexican Midwifery Center Organization Amidst the COVID-19 Crisis - Alonso, Cristina; Storey, Akane Sugimoto; Fajardo, Ilse; Borboleta, Hannah S. (Frontiers in Sociology, 2021)
Luna Maya is a Mexican NGO that operates two full-scope midwifery centers in Mexico City and Chiapas, Mexico, providing woman-centered, culturally appropriate midwifery model maternity care on a sliding cost scale. The COVID-19 health crisis has made it necessary for Luna Maya to quickly incorporate safety protocols for out-of-hospital maternity care. Yet many of the emerging guidelines on maternity care have focused on high-income and hospital settings; there are no specific guidelines for such care in out-of-hospital settings in low- and middle-income countries. Thus we have had to create our own based on best available and emerging evidence. In this article, we describe the guidelines and protocols we have created in response to COVID-19, the international evidence and recommendations on which we base them, and precisely how we carry them out in practice. We also present and analyze the results of qualitative interviews we conducted for this article with eight of our midwives and eight of our midwifery clients. These interviews reveal the tremendous stresses both midwives and pregnant and birthing women are experiencing as a result of the pandemic, their creative adaptations, and the structural flaws, deficiencies, and inequities of the Mexican healthcare system. The article also addresses Luna Maya’s ongoing challenges in continuing to provide care completely outside of governmental support and in difficult economic times, and demonstrates the extreme need for improvements in the Mexican system of maternity care and for full integration of community-based midwives and out-of-hospital birth.